The condition, planning and design of Trifković Square in Novi Sad for the purpose of developing tourism - Garača, Vuk; Vukosav, Svetlana; Tepavčević, Jelena; Bradić, Milan (Arhitektura i urbanizam, 2026)
Trifkovic Square is part of the city of Novi Sad and its old city area. As such, the Square has a long history and a very characteristic way of its formation and cultural and historical values, which, among other locations, place it in the focus of tourism development in Novi Sad. The subject of the research is the clearly spatially limited entity of Trifkovic Square in Novi Sad. The aim of the paper is to present one of the possible ways of arranging the given space for the needs and in the function of tourism development, which has been constantly growing in Novi Sad for the last 15 years. The tasks of the paper are to present the historical context of the creation and development of Trifkovic Square in Novi Sad, to analyze its current state in terms of location, function, urban furniture, greenery, as well as planning documents that take into account this spatial unit in the central core of Novi Sad. The research was conducted on the basis of published studies and available documentation, which deal with similar issues. Based on the collected data, a systematic analysis of the space was carried out, its cartographic and photographic presentation was made, and proposals were made for its further development and functional organization. The aim of the paper is to point out the importance of this part of Novi Sad for the development of tourism and its possible inclusion in tourist flows, through existing and some future planning solutions.